The Effectiveness of Sports Student Activity Unit Programs in Improving Student-Athlete Achievement - Rahmi, Silatul; Hanafi, Suriah (SHOOTING: Journal of Sport, Health, and Education, 2025)
This research aims to analyze the effectiveness of Sports Student Activity Unit (UKM) programs in improving student-athlete achievement at the Faculty of Sports Science and Health (FIKK) Universitas Negeri Makassar (UNM). Sports UKM has a strategic role as a forum for coaching and developing student sports talents in higher education. This research uses a quantitative approach with an evaluative descriptive method on 120 student-athletes who actively participate in Sports UKM at FIKK UNM selected using proportionate stratified random sampling technique. Data were collected through questionnaires, structured interviews, achievement documentation, and field observations. The research instruments include aspects of training programs, facilities and infrastructure, coach quality, organizational management, and institutional support that have been tested for validity and reliability. Data analysis uses descriptive percentage analysis and program effectiveness analysis with the Context, Input, Process, Product (CIPP) model. The research results show that the Sports UKM program at FIKK UNM is in the effective category with an effectiveness percentage of 78.4%. The most effective component is coach quality with a percentage of 82.6%, while the component that needs improvement is facilities and infrastructure with a percentage of 71.3%. Student-athlete achievements show significant improvement with the acquisition of 45 medals in various regional and national championships over the past two years. This research concludes that the Sports UKM program makes a positive contribution to improving student-athlete achievement, but improvements are still needed in aspects of facilities and infrastructure and a more structured coaching system